2022
DOI: 10.3389/fimmu.2022.869207
|View full text |Cite
|
Sign up to set email alerts
|

Acinar Cell-Derived Extracellular Vesicle MiRNA-183-5p Aggravates Acute Pancreatitis by Promoting M1 Macrophage Polarization Through Downregulation of FoxO1

Abstract: Acute pancreatitis (AP) is a common cause of a clinically acute abdomen. Crosstalk between acinar cells and leukocytes (especially macrophages) plays an important role in the development of AP. However, the mechanism mediating the interaction between acinar cells and macrophages is still unclear. This study was performed to explore the role of acinar cell extracellular vesicles (EVs) in the crosstalk between acinar cells and macrophages involved in the pathogenesis of AP. EVs derived from caerulein-treated aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The lactate produced by tumor glycolysis, serving as a proinflammatory and immunosuppressive mediator within the tumor microenvironment, is modulated by METTL14-mediated m6A methylation, influencing the polarization of macrophages. 27 Our study identifies that METTL14 and m6A modification are significantly downregulated in CC and that there is a correlation between METTL14 levels and poor prognosis in CC. Another study highlighted that hypoxia suppresses METTL14 in a HIF-1α-dependent manner and that METTL14 mediates m6A modification of SLC7A11 mRNA at its 5′-UTR, leading to a decrease in SLC7A11 expression via a YTHDF2-dependent pathway, thus inhibiting ferroptosis in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 59%
“…The lactate produced by tumor glycolysis, serving as a proinflammatory and immunosuppressive mediator within the tumor microenvironment, is modulated by METTL14-mediated m6A methylation, influencing the polarization of macrophages. 27 Our study identifies that METTL14 and m6A modification are significantly downregulated in CC and that there is a correlation between METTL14 levels and poor prognosis in CC. Another study highlighted that hypoxia suppresses METTL14 in a HIF-1α-dependent manner and that METTL14 mediates m6A modification of SLC7A11 mRNA at its 5′-UTR, leading to a decrease in SLC7A11 expression via a YTHDF2-dependent pathway, thus inhibiting ferroptosis in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 59%
“…23,24 The secretion of exosome-specific inflammatory miRNAs by inflammatory cells and exosome-specific antiinflammatory miRNAs by parenchymal cells is only sometimes definitive, and their functions may occasionally be International Journal of Nanomedicine 2023:18 https://doi.org/10.2147/IJN.S428924 DovePress 6755 interchanged. Tang et al 25 discovered that miR-183-5p, specific to EVS and derived from acinar cells, can induce macrophage polarization towards M1. This is achieved through the inhibition of forkhead box transcription factor O1 (FoxO1) expression, which ultimately exacerbates the severity of SAP.…”
Section: Discussionmentioning
confidence: 99%
“…The application of a Notch inhibitor, such as DAPT, has been reported to alleviate symptoms of AP. Additionally, recent studies have shown that the release of extracellular vesicles (EVs) containing miR-183-5p increases in acinar cells during cerulein treatment, inducing the M1 polarization of macrophages and subsequently causing acinar cell damage [ 44 ]. This emerging evidence underscores the complex interplay of molecular signals that modulate macrophage polarization and their potential implications in AP therapy.…”
Section: Macrophage Activation In Pancreatitis and Its Regulatorsmentioning
confidence: 99%